Implementasi Prinsip Good Governance dalam Manajemen Koperasi Syariah - Hani Rafika Santi; Adib Sulistyo; Adi Wiratno (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis, Universitas Jenderal Soedirman, Indonesia, 2025)
This study analyzes the implementation of good governance principles comprising transparency, accountability, responsibility, independence, and fairness in the management of KSPPS BMT FEB Universitas Muhammadiyah Purwokerto using a qualitative descriptive approach. Data were collected through in-depth interviews with key informants, non-participant observation, and comprehensive document analysis. The findings show that BMT FEB UMP implements all five good governance principles in its operational practice, though with varying intensity and maturity levels. Responsibility, particularly in the dimension of sharia compliance, shows the strongest and most consistent implementation, followed by transparency and accountability. The presence of an active and competent Sharia Supervisory Board strengthens good governance implementation across all dimensions, providing deeper spiritual and ethical value to organizational governance. Sharia governance functions not merely as an additional control mechanism, but is integral and mutually reinforcing with good governance in creating a coherent and meaningful governance ecosystem. Despite challenges such as regulatory conflicts between conventional cooperative law and sharia principles, human resource limitations, and fluctuating student membership, strong institutional support from the academic community and organizational commitment to sharia principles enable BMT to continuously develop and innovate with product diversification and improved service quality.